Absolute C++ - Savitch, Walter J., 1943- (Pearson Education Limited, 2016)
For courses in computer programming for business and engineering. Introduction and Advancement in C++ Programming Absolute C++ is a comprehensive introduction to the C++ programming language. The text is organized around the specific use of C++, providing students with an opportunity to master the language completely. Adaptable to a wide range of users, the text is appropriate for beginner to advanced programmers familiar with the C++ language. The Sixth Edition covers everything from basic syntax to more advanced topics, such as polymorphism, exception handling, and the Standard Template